Benchmarking money manager performance : issues and evidence - Chan, Louis K. C. (2013)
Academic and practitioner research yields a proliferation of methods using size and value/growth attributes or factors to evaluate portfolio performance. We assess the relative merits of several of the most widely-used procedures, including variants of matched-characteristic benchmark portfolios and time-series return regressions, by applying them to a sample of active money managers and passive indexes. Estimated abnormal returns display large variation across approaches. The benchmarks most widely used in academic research - attribute-matched portfolios from independent sorts, the conventional three-factor time series model, and cross-sectional regressions of returns on stock characteristics - have poor ability to track returns. Simple alterations are provided that improve the performance of the methods.